2000
DOI: 10.1034/j.1600-0420.2000.078004437.x
|View full text |Cite
|
Sign up to set email alerts
|

Iris indocyanine green angiography in pseudoexfoliation syndrome and capsular glaucoma

Abstract: ABSTRACT.Purpose: The iris vasculature shows typical changes in pseudoexfoliation syndrome (PXS) revealed by iris fluorescein angiography (IFA), such as hypoperfusion, microneovascularisation, and anastomotic vessels. Iris indocyanine green angiography (IICGA) can visualize more precisely details of the iris vascular pattern, especially as regards hypoperfusion and capillary dilatations. The aim of the present study is to describe the angiographic features of PXS on IFA and IICGA, comparing eyes affected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
2
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 17 publications
1
19
2
4
Order By: Relevance
“…10,11 In the current investigation, we have tried to assess if there is a gradual progression of the severity of microvascular abnormalities in the different stages of the disease. The results of quantitative analyses show that unaffected, affected, and bilateral groups are quite similar, whereas eyes affected by PES glaucoma have more severe involvement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…10,11 In the current investigation, we have tried to assess if there is a gradual progression of the severity of microvascular abnormalities in the different stages of the disease. The results of quantitative analyses show that unaffected, affected, and bilateral groups are quite similar, whereas eyes affected by PES glaucoma have more severe involvement.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The reported histological changes are the morphological correlate of the blood-aqueous barrier (BAB) breakdown, which can be studied by means of several techniques, including fluorophotometry, 3 laser flare-cell meter, [4][5][6] immunohistochemical tracer, 7 and iris angiography. 3,[8][9][10][11] Typical features of PES on iris angiography are hypoperfusion, microneovascularizations, and anastomotic vessels. 3,[9][10][11] Comparison between iris fluorescein angiography (IFA) and iris indocyanine green angiography (IICGA) has shown that IICGA is superior in disclosing iris hypoperfusion and anastomotic vessels, whereas IFA allows a more precise detection of microneovascularizations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluorescein angiography reveals hypoperfusion, apparent microneovascularization, fluorescein leakage, and vascular anastomosis of iris vessels. [7][8][9][10][11] There is apparent microneovascularization of the limbus as well as ectasia and tortuosity of ciliary vessels. 12 Central retinal vein occlusions occur more commonly in XFS vs controls.…”
Section: Introductionmentioning
confidence: 99%